Preparation, characterization, and osteogenic activity mechanism of casein phosphopeptide-calcium chelate - Huang, Wen; Lao, Linhui; Deng, Yuliang; Li, Ziwei; Liao, Wanwen; Duan, Shan; Xiao, Suyao; Cao, Yong; Miao, Jianyin (Frontiers in Nutrition, 2022)
Casein phosphopeptides (CPPs) are good at calcium-binding and intestinal calcium absorption, but there are few studies on the osteogenic activity of CPPs. In this study, the preparation of casein phosphopeptide calcium chelate (CPP-Ca) was optimized on the basis of previous studies and its peptide-calcium chelating activity was characterized. Subsequently, the effects of CPP-Ca on the proliferation, differentiation and mineralization of MC3T3-E1 cells were studied, and the differentiation mechanism of CPP-Ca on MC3T3-E1 cells was further elucidated by RNA sequencing (RNA-seq). The results showed that the calcium chelation rate of CPPs was 23.37%, and the calcium content of CPP-Ca reached 2.64×105 mg/kg. The test results of Ultraviolet–Visible absorption spectroscopy (UV) and Fourier transform infrared spectroscopy (FTIR) indicated that carboxyl oxygen and amino nitrogen atoms of CPPs might be chelated with calcium during the chelation. Compared with the control group, the proliferation of MC3T3-E1 cells treated with 250 µg/mL of CPP-Ca increased by 21.65%, 26.43% and 28.43% at 24, 48 and 72 h, respectively, and the alkaline phosphatase (ALP) activity and mineralized calcium nodules of MC3T3-E1 cells were notably increased by 55% and 72%. RNA-seq results showed that 321 differentially expressed genes (DEGs) were found in MC3T3-E1 cells treated with CPP-Ca, including 121 up-regulated genes and 200 down-regulated genes. Gene ontology (GO) functional revealed that the DEGs mainly played important roles in the regulation of cellular components. Kyoto Encyclopedia of Genes and Genomes Database (KEGG) pathway enrichment indicated that the AMPK, PI3K-Akt, MAPK and Wnt signaling pathways were involved in the differentiation of MC3T3-E1 cells. The results of quantitative real-time PCR (qRT-PCR) showed that compared with the blank control group, the mRNA expressions of Apolipoprotein D (APOD), Osteoglycin (OGN) and Insulin like growth factor (IGF1) were significantly increased by 2.6, 2.0 and 3.0 times, respectively, while the mRNA levels of NOTUM, WIF1, LRP4 notably decreased to 2.3, 2.1 and 4.2 times, respectively, which were consistent both in GO functional and KEGG enrichment pathway analysis. This study provided a theoretical basis for CPP-Ca as a nutritional additive in the treatment and prevention of osteoporosis.